Game-theoretical mapping of fundamental brain functions based on lesion deficits in acute stroke. Issue 3 (2nd September 2021) - Malherbe, Caroline; Cheng, Bastian; Königsberg, Alina; Cho, Tae-Hee; Ebinger, Martin; Endres, Matthias; Fiebach, Jochen B; Fiehler, Jens; Galinovic, Ivana; Puig, Josep; Thijs, Vincent; Lemmens, Robin; et al.
Abstract: Lesion analysis is a fundamental and classical approach for inferring the causal contributions of brain regions to brain function. However, many studies have been limited by the shortcomings of methodology or clinical data. Aiming to overcome these limitations, we here use an objective multivariate approach based on game theory, Multi-perturbation Shapley value Analysis, in conjunction with data from a large cohort of 394 acute stroke patients, to derive causal contributions of brain regions to four principal functional components of the widely used National Institutes of Health Stroke Score measure. The analysis was based on a high-resolution parcellation of the brain into 294 grey and white matter regions. Through initial lesion symptom mapping for identifying all potential candidate regions and repeated iterations of the game-theoretical approach to remove non-significant contributions, the analysis derived the smallest sets of regions contributing to each of the four principal functional components as well as functional interactions among the regions. Specifically, the factor 'language and consciousness' was related to contributions of cortical regions in the left hemisphere, including the prefrontal gyrus, the middle frontal gyrus, the ventromedial putamen and the inferior frontal gyrus. Right and left motor functions were associated with contributions of the left and right dorsolateral putamen and the posterior limb of the internal capsule, correspondingly. Moreover, the superior corona radiata and the paracentral lobe of the right hemisphere as well as the right caudal area 23 of the cingulate gyrus were mainly related to left motor function, while the prefrontal gyrus, the external capsule and the sagittal stratum fasciculi of the left hemisphere contributed to right motor function. Our approach demonstrates a practically feasible strategy for applying an objective lesion inference method to a high-resolution map of the human brain and distilling a small, characteristic set of grey and white matter structures contributing to fundamental brain functions. In addition, we present novel findings of synergistic interactions between brain regions that provide insight into the functional organization of brain networks. Abstract : Malherbe et al. report a feasible strategy for applying an objective multivariate lesion inference method, using game theory and bootstrapping, to a high-resolution map of the human brain and distilling a small characteristic set of grey and white matter structures contributing to fundamental brain functions, without external preselection of regions. Graphical Abstract: